Bending behaviours of load-carrying fillet welds around misaligned hollow structural sections. (February 2023) - Wang, Zhi-Yu; Shi, Yun-Zhong; Zhao, Qiu-Hong; Yao, Guo-Wen; He, Ming-De; Zhou, Xia-Fang
Abstract: Misaligned hollow structural section (HSS) chords have gained increasingly application in the tubular joist structures connecting panelised façades. Despite the fillet welds are known to be efficient in connecting the HSS structures, the bending behaviours and fracture characteristics of welded misaligned HSSs have not been clearly understood for their engineering practice. This paper presents the results of an experimental and finite element (FE) modelling study with focus on the combined stress states of the misaligned HSS and the critical weld throat plane in its connecting welds. The configurations for the corner connection and the interior wide connection were compared in terms of their failure modes and load–deflection response. A theoretical analytical approach for predicting the combined stress of the misaligned HSS chord and the fillet weld in the connection subjected to flexural, shear and torsional loading is proposed and shown to achieve a good correlation. Based on the results of validated FE models, the traction stresses of fillet welds with appropriate allowance of the weld eccentricity induced secondary moment are demonstrated to give a better replication of the stress distribution of the critical weld throat plane. Finally, it has been found from a FE parametric analysis that the local stress concentration at the critical weld throat plane can be significantly amplified with increased weld flank angle, decreased HSS chord thickness-to-width ratio, increased misalignment angle of HSS chord or reduced relative weld leg length, in which the last two influential factors notably contribute to the elevation of stress concentration.